Effect of Pre-exposure Use of Amantadine on COVID-19 Infection: A Hospital-Based Cohort Study in Patients With Parkinson's Disease or Multiple Sclerosis - Kamel, Walaa A.; Kamel, Mohmed I.; Alhasawi, Almunther; Elmasry, Sameh; AlHamdan, Fajer; Al-Hashel, Jasem Y. (Frontiers in Neurology, 2021)
Background: Amantadine has been proposed to inhibit E-channel conductance in reconstituted lipid bilayers of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We aimed to study whether patients on amantadine have altered risks of contracting COVID-19 infection. Methods: We conducted a hospital-based, observational, retrospective cohort study using data for patients on amantadine supported by data given by the patients through an online questionnaire. We included registered amantadine users in our hospital for 6 months or more on March 1, 2020, and non-amantadine users to act as the control group. We used forced entry, multiple logistic regression models to estimate adjusted ORs for amantadine adjusting for the confounders. Findings: Between September 1, 2019, and March 1, 2020, 212 patients with Parkinson's disease (PD) or multiple sclerosis (MS) received greater than one equal to two prescriptions of amantadine. We selected a random sample of diagnoses which matched 424 patients of non-amantadine users (1:2) as a control group (424 patients). Between March 1, 2020, and March 1, 2021, 256 patients responded to our online questionnaire, 87 patients were on amantadine (group I), and 169 patients were not (control group, group II). COVID-19 disease infection proved to be 5.7 and 11.8% in group I and II patients, respectively. Increased odds of COVID-19 in multivariable-adjusted models were associated with old age and history of contact with COVID cases. Amantadine was associated with a significantly reduced risk of COVID-19 disease infection (adjusted OR 0.256, 95% CI 0.074–0.888). Interpretation: Amantadine is associated with a reduced risk of COVID-19 infection after adjusting for a broad range of variables. History of contact with COVID cases and old age are risk factors for COVID-19 infection. Therefore, we recommended randomized clinical trials investigating amantadine use for the prevention of COVID-19.